Optimum Savings Under Uncertainty: A Correction - Levhari, D.; Srinivasan, T. N. (Review of Economic Studies, 1977)
D. Levhari, T. N. Srinivasan; Optimum Savings Under Uncertainty: A Correction, The Review of Economic Studies, Volume 44, Issue 1, 1 February 1977, Pages 1